The Heisenberg Relation - Mathematical Formulations - Kadison, R.V.; Liu, Z. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We study some of the possibilities for formulating the Heisenberg relation of quantum mechanics in mathematical terms. In particular, we examine the framework discussed by Murray and von Neumann, the family (algebra) of operators affiliated with a finite factor (of infinite linear dimension).